1990
DOI: 10.1159/000181795
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Subclinical Signs of Autonomic Neuropathy in the Early Stage of Childhood Diabetes

Abstract: It has been suggested that subclinical signs of neuropathy appear earlier than microvascular complications of diabetes. To evaluate the occurrence of autonomic nervous system dysfunction in the early stage of childhood diabetes, subclinical signs of autonomic neuropathy (resting heart rate, hyperventilatory arrhythmia, standing/lying heart rate ratio, orthostatic decrease in blood pressure, and increase in blood pressure during sustained handgrip) were investigated in 54 children with type 1 diabetes divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…On the other hand, controversial data exist regarding the influence of diabetes duration and metabolic control on these neurological abnormalities [12,22,24,27,29]. The present study is in accordance with our previous findings [2,5] and suggests that autonomic dysfunction is related to the duration of diabetes and long-term metabolic conrol. Both cardiovascular and urogenital autonomic neuropathy have a poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, controversial data exist regarding the influence of diabetes duration and metabolic control on these neurological abnormalities [12,22,24,27,29]. The present study is in accordance with our previous findings [2,5] and suggests that autonomic dysfunction is related to the duration of diabetes and long-term metabolic conrol. Both cardiovascular and urogenital autonomic neuropathy have a poor prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Confidence limits of 95% (2SD) from means of control subjects were considered as limits of normality. Deviations exceeding 2SD from the normal mean were considered abnormal [5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Little information is available about diabetic children with a shorter duration of disease in whom neuropathy is rare. In addition, few studies have yet reported data on respiratory control in childhood diabetes [23].…”
mentioning
confidence: 99%
“…In adolescents with diabetes, evidence for cardiovascular autonomic nerve involvement has come from an increase in test abnormalities (29–31%) [2, 3] and from differences between diabetic and control groups [3, 4, 5]. However, there is less evidence for persisting dysfunction or declining function in longitudinal studies.…”
Section: Studies Of Cardiovascular Reflexesmentioning
confidence: 99%